PSYCHOLOGICAL CHARACTERISTICS OF SCHOOL STUDENTS - Dustkobilov Rustam Dusmamat ugli (Western European Studies, 2025)
This article analyzes the psychological characteristics of schoolchildren, their formation processes and development dynamics. The importance of individual psychological aspects of students - temperament, character, abilities, interests, emotional states and selfawareness mechanisms in the educational process is highlighted. The socio-psychological influence of the family, school and peer group on the formation of the personality of students is also analyzed. The article describes the stages of psychological development of school-age children and pedagogical approaches appropriate to them based on modern psychological research. The results of the study help teachers take into account the individual characteristics of students in the educational process and serve to form effective communication and a personal approach
Keywords: schoolchildren; psychological characteristics; personality development